New Soviet Citizen Survey, 1990: Problems of Peace and Security - Miller, Arthur H. ([Verlag nicht ermittelbar], 1994)
For this study, over 1,800 adult citizens were interviewed in three Soviet republics: Lithuania, the Ukraine, and the portion of Russia west of the Ural Mountains. Questions focused on several topics facing the new republics, including pressing domestic problems, relations among republics and Moscow, feelings about the past and future directions of the economy, feelings toward various organized groups in the former Union of Soviet Socialist Republics (USSR), and attitudes regarding disarmament and military service. Also included are demographic variables for respondents, such as age, occupation, and income.